2018
DOI: 10.1097/shk.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Colonization of Candida Albicans Increases Serum (1→3)-β-D-Glucan, without Candidemia, and Worsens Cecal Ligation and Puncture Sepsis in Murine Model

Abstract: The role of intestinal Candida albicans in bacterial sepsis, in the absence of candidemia, was investigated in murine models. Live C albicans or normal saline solution (NSS) was administered orally once, followed by 5 days of daily oral antibiotic-mixtures (ATB). Cecal ligation and puncture (CLP) was then performed to induce sepsis.Fecal Candida was detected by culture only in models with Candida administration. Oral Candida administration with/without ATB enhanced gut-pathogenic bacteria as determined by micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 35 publications
4
74
0
Order By: Relevance
“…Our data suggest that, apart from older age, the only variable associated with septic shock in candidemic patient was an intra-abdominal origin of the infection. This result supports recent experimental observations that intestinal abundance of Candida may be associated with an increased sepsis severity, perhaps through cytokine storm induction and/or decreased macrophage killing activity [29][30][31]. The fact that patients with other source of the infection (i.e., CVC or urinary tract) received a similar rate of adequate source control of candidemia (43.4% vs 40.5%, p = 0.86) and even a lower rate of adequate antifungal treatment (38.1% vs 61.5%, p = 0.008) is further consistent with this intriguing explanation.…”
Section: Discussionsupporting
confidence: 91%
“…Our data suggest that, apart from older age, the only variable associated with septic shock in candidemic patient was an intra-abdominal origin of the infection. This result supports recent experimental observations that intestinal abundance of Candida may be associated with an increased sepsis severity, perhaps through cytokine storm induction and/or decreased macrophage killing activity [29][30][31]. The fact that patients with other source of the infection (i.e., CVC or urinary tract) received a similar rate of adequate source control of candidemia (43.4% vs 40.5%, p = 0.86) and even a lower rate of adequate antifungal treatment (38.1% vs 61.5%, p = 0.008) is further consistent with this intriguing explanation.…”
Section: Discussionsupporting
confidence: 91%
“…Although the increased sepsis severity in our models could be responsible from fungal factors (fecal Candida burdens and serum BG) and/or bacterial factor (gut microbiome alteration), the data from the CLP- Candida model that i) the oral administration of live- or heat killed- Candida increased sepsis severity and ii) the reduction of fecal Candida with fluconazole, without additional antibacterial drugs, attenuated sepsis severity implied a more prominent influence of fungal factors over bacterial factor in bacterial sepsis severity in our models. It is also interesting to note that the impact of intestinal Candida on bacterial sepsis severity was also more predominant than the effect from fecal-microbiome alteration in the 5 days Candida colonization model, a model with the influence of mixed-oral antibiotics [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that oral administration of C . albicans with mixed-oral antibiotics 5 days prior to cecal ligation and puncture (CLP) enhances the severity of bacterial sepsis in the murine sepsis model [ 14 ]. However, oral antibiotics, alone, impact fecal microbiota and sepsis severity in the Candida colonization model [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As alluded too by Cortegiani et al, beta-D-glucan (BDG) could be a very good candidate associated to PCT. Indeed, BDG could be even a better candidate as its molecular weight ranges from several hundred thousand to 10 million daltons and does not pass through any membrane [4,5]. Finally, we would like to add that BDG can be also be falsely elevated in case of gastrointestinal colonization of Candida albicans that increases serum BDG without candidemia [5].…”
mentioning
confidence: 99%